Mesoporous TUD-1 supported indium oxide nanoparticles for epoxidation of styrene using molecular O-2 - Rahman, Sumbul; Farooqui, Saleem A.; Rai, Aditya; Kumar, Rawesh; Santra, Chiranjit; Prabhakaran, Vinod C.; Bhadu, Gopala Ram; Sen, Debasis; Mazumder, S.; Maity, Sudip; Sinha, Anil K.; Chowdhury, Biswajit (RSC Advances, 2015)
Activation of molecular O-2 by metal or metal oxide nanoparticles is an area of recent research interest. In this work, for the first time, we report that indium oxide nanoparticles of <3 nm size dispersed on mesoporous silica (TUD-1) can activate molecular O-2 and produce styrene epoxide with a selectivity of 60% and styrene conversion around 25% under mild conditions. It is found that neither indium oxide nor TUD-1 themselves respond to the styrene epoxidation reaction. The computational studies provide evidence that an oxygen molecule is highly polarized when it is located near the interface of both surfaces. The kinetic study shows that the reaction is of pseudo-first order and that the activation energy for styrene conversion is 12.138 kJ mol(-1). The catalysts are recyclable for up to four regeneration steps, with the styrene conversion and styrene epoxide selectivity almost unchanged.

Heterogeneous route for transfer hydrogenation reactions of ketones using Ru(II)Cymene complex over modified benzene-organosilica (PMOB) - Lazar, Anish; Silpa, S.; Prabhakaran, Vinod C.; Singh, A. P. (Molecular Catalysis, 2017)
An inorganic-organic hybrid catalyst, Ru(II)Cym@PMOB, was synthesized by anchoring of [Ru(II)Cl-2(Pcymene)](2) complex which is derived from a reaction between hydrated ruthenium(III) trichloride and ocphellandrene over aminofunctionalized benzene-organosilica (PMOB). In the context of secondary alcohol synthesis from ketones, transfer hydrogenation (TH) reactions are convenient compared to conventional hydrogenation reactions owing to its lower activation energy and ambient pressure and mild temperature reaction" conditions. The synthesized catalysts were characterized by CHN analysis, XRD, ICP, N-2-sorption analysis, TG & DTA, FFIR,C-13 & 29Si solid NMR, UV-vis, TEM, SEM and XPS. The catalytic activities of neat [Ru(II)C-12(p-cymene)]2 complex and Ru(II)Cym@PMOB were evaluated in transfer hydrogenation (TH) of ketones (-97%) and compared with conventional hydrogenation reactions (-5%) where molecular H-2 was used. The results showed Ru(II)Cym@PMOB as highly active catalyst towards transfer hydrogenation (TH) reaction of acetophenones compared to neat [Ru(II)Cl-2(p-cymene)(12) complex. The heterogeneity of Ru(II)Cym@PMOB was confirmed by Sheldon's test. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Conventional Hydrogenation Reactions; Ru(II)Cym@PMOB; Transfer Hydrogenation Reaction; [Ru(II)Cl2(p-cymene)]2 complex

Palladium impregnated amine Co-condensed hexagonal mesoporous silica: a novel catalyst in tailoring suzuki and heck coupling reactions in base free condition - Das, Prangya Paramita; Prabhakaran, Vinod C.; Nanda, Samik; Sen, Debasis; Chowdhury, Biswajit (ChemistrySelect, 2019)
Palladium impregnated amine co-condensed hexagonal mesoporous silicas (HMS-X) were synthesized (sol-gel process) using different amines (Ethylene diamine and pyridine) of various concentrations (0.25 equiv. and 2 equiv.). The effect of amine concentration on the local structure of hexagonal mesoporous silica was studied. The catalyst shows excellent catalytic activity and high TOF towards both Suzuki and Heck coupling reactions without using any base in reaction medium with the solvent DMF:water in (1:1) ratio. The catalyst was reused and it was recyclable up to three cycle without any appreciable loss of activity and the kinetics of the reaction varying different parameters also have been studied thoroughly.
Keywords: Amine functionalized silica; Base free; Heck reaction; Palladium supported catalysts; Suzuki reaction

Heterostructure from heteromixture: unusual OER activity of FeP and CoP nanostructures on physical mixing - Bhutani, Divya; Maity, Sisir; Chaturvedi, Shashank; Chalapathi, Divya; Waghmare, V. Umesh; Narayana, Chandrabhas; Prabhakaran, Vinod C.; Muthusamy, Eswaramoorthy (Journal of Materials Chemistry A, 2022)
Heterointerfaces generated by inter-domain interactions on a nanoscale play a critical role in altering the activity of an electrocatalyst towards an electrochemical process. Heterointerfaces affect the surface characteristics, electronic structure, and physicochemical properties of a nanomaterial. Herein, we report an FeP-CoP heterostructure prepared by simple physical mixing of FeP and CoP nanostructures showing a remarkable performance towards water oxidation in comparison to their individual monometallic phosphides. FeP mixed with 20 wt% CoP shows a low overpotential (eta(10)) of 220 mV as compared to FeP (eta(10), 325 mV). Furthermore, a high current density of 1.37 A cm(-2) and mass activity of 18 987 A g(M)(-1) were also achieved at 500 mV overpotential in 1.0 M KOH. The physical mixture shows immense stability for 200 h to achieve a high current density of 200 mA cm(-2). Meanwhile the potentiostatic performance of FeP at 200 mA cm(-2) decreases to an extent of 50% in 40 h. A full cell arrangement employing this catalyst as the anode material requires 1.56 V to attain a current density of 10 mA cm(-2). Various characterization techniques, control experiments and theoretical studies indicate that the formation of heterointerfaces between the nano-domains of FeP and CoP results in charge transfer between Fe and Co metal sites. In addition, an oxygenated surface at the metal phosphide interface favours the sorption kinetics of intermediates involved in the reaction leading to low energy barriers in the potential determining and other steps, thus showing improved performance towards water oxidation.